Linguistic politeness across boundaries : the case of Greek and Turkish - Bayraktaroğlu, Arın, 1945-; Sifianou, Maria (Pragmatics & beyond, 2001)
This volume includes 14 papers investigating politeness phenomena in Greece and Turkey, the cultural cross-roads of Europe, Asia and the Middle East. It reflects current research and provides observations of and findings in patterns of linguistic politeness in a geographical area other than the much studied English speaking ones. The book appeals to professionals and students interested in a broader perspective of language use in its social context. Articles in the collection are empirically rather than theoretically oriented and examine realisations of politeness in relation to social paramet.